Photocatalytic Degradation of Aniline Using TiO2 Nanoparticles in a Vertical Circulating Photocatalytic Reactor - F. Shahrezaei; Y. Mansouri; A. A. L. Zinatizadeh; A. Akhbari (International Journal of Photoenergy)
Photocatalytic degradation of aniline in the presence of titanium dioxide (TiO2) and ultraviolet (UV) illumination was performed in a vertical circulating photocatalytic reactor. The effects of catalyst concentration (0–80 mg/L), initial pH (2–12), temperature (293–323 K), and irradiation time (0–120 min) on aniline photodegradation were investigated in order to obtain the optimum operational conditions. The results reveal that the aniline degradation efficiency can be effectively improved by increasing pH from 2 to 12 and temperature from 313 to 323 K. Besides, the effect of temperature on aniline photo degradation was found to be unremarkable in the range of 293–313 K. The optimum catalyst concentration was about 60 mg/L. The Langmuir Hinshelwood kinetic model could successfully elucidate the effects of the catalyst concentration, pH, and temperature on the rate of heterogeneous photooxidation of aniline. The data obtained by applying the Langmuir Hinshelwood treatment are consistent with the available kinetic parameters. The activated energy for the photocatalytic degradation of aniline is 20.337 kj/mol. The possibility of the reactor use in the treatment of a real petroleum refinery wastewater was also investigated. The results of the experiments indicated that it can therefore be potentially applied for the treatment of wastewater contaminated by different organic pollutants.